Hubungan Komunikasi Terapeutik dan Risiko Perilaku Kekerasan pada Pasien Skizofrenia di Rumah Sakit Jiwa Provinsi Bali - Dewa GD Putra Jatmika; Komang Yogi Triana; Ni Komang Purwaningsih (Poltekkes Kemenkes Bengkulu, 2020)
Violent behavior is one of symptoms that can be demonstrated by patients with schizophrenia which it can cause injury to the patient and others. Therapeutic communication is one of the nursing intervention for patients with violent behavior. This study aimed to identify the relationship of communication and risk of violent behavior in schizophrenic patients. This study used a descriptive correlational with a cross-sectional design, which involved 68 patients with schizophrenia who were selected by consecutive sampling technique. The instrument in this study used a therapeutic communication checklist and observation sheets for changes in violent behavior. The results showed that as many as 35 patients (51.5%) who received good therapeutic communication from nurses, and 37 (54.4%) patients showed moderate risk of violent behavior. The results of the analysis by the Gamma ordinal by ordinal test found that there was a significant relationship between therapeutic communication and the risk of violent behavior with p value= 0.001 (<0.05). It showed that the better therapeutic communication applied, the lower of the incidence of violent behavior in schizophrenic patients. Thus it is expected that nurses can practice therapeutic communication techniques to improve the patient's condition so that violent behavior in patients can be reduced.